Superoxide Dismutases in Eukaryotic Microorganisms: Four Case Studies - Alvaro de Obeso Fernandez del Valle; Christian Quintus Scheckhuber (MDPI AG, 2022)
Various components in the cell are responsible for maintaining physiological levels of reactive oxygen species (ROS). Several different enzymes exist that can convert or degrade ROS; among them are the superoxide dismutases (SODs). If left unchecked, ROS can cause damage that leads to pathology, can contribute to aging, and may, ultimately, cause death. SODs are responsible for converting superoxide anions to hydrogen peroxide by dismutation. Here we review the role of different SODs on the development and pathogenicity of various eukaryotic microorganisms relevant to human health. These include the fungal aging model, Podospora anserina; various members of the genus Aspergillus that can potentially cause aspergillosis; the agents of diseases such as Chagas and sleeping disease, Trypanosoma cruzi and Trypanosoma brucei, respectively; and, finally, pathogenic amoebae, such as Acanthamoeba spp. In these organisms, SODs fulfill essential and often regulatory functions that come into play during processes such as the development, host infection, propagation, and control of gene expression. We explore the contribution of SODs and their related factors in these microorganisms, which have an established role in health and disease.